Weekend in Taipei [videorecording (DVD)] - Evans, Luke, 1979-; Gui, Lunmei, 1983-; Kang, Sung, 1972- (Ketchup Entertainment, 2025)
On undercover assignment, DEA agent John Lawlor fell in love with Josephine 'Joey' Kwang, one of Taipei's best transport drivers. Forced to flee, John is now back. But is he here to finish the job? Or to win back Joey's love?